COUNSELLING COGNITIVE BEHAVIOR THERAPY IN INCREASING SELF-CONTROL WITH INTENSIVE BULLYING BEHAVIOUR - Suhaili, Suhaili; Majdi, M. Zuhdi Zainul (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
Bullying has long been an obstacle in how schools operate. Bullying as a phrase describes a variety of ways in which someone uses strength or power to hurt somebody else, leaving the victim feeling hopeless, traumatized, and unhappy. The goal of the study was to determine the effectiveness of cognitive behavior therapy counseling to increase self-control in students who have a tendency of bullying behavior. This study used a pretest and multiple posttest design. Seven children were used as the study's subjects. Purposive sampling was utilized for the sample elimination. Questionnaires on self-control and bullying were used to collect data. Statistical analysis of data using the repeated measures anova test. The findings demonstrated that cognitive behavior therapy counseling was contributing to improve self-control within individuals who had shown a tendency towards bullying behavior.